The human serotonin receptor 2B: coding region polymorphisms and association with vulnerability to illegal drug abuse - Lin, Zhicheng; Walther, Donna; Yu, Xiao-Ying; Drgon, Tomas; Uhl, George R (Pharmacogenetics, 2004)
OBJECTIVE AND METHODS: 5-Hydroxytryptamine (serotonin) receptor 2B (HTR2B) is involved in brain development. Although expressed in the human brain, HTR2B has not been investigated much for its role in higher brain functions. Here we describe a genome-scan with 391 simple sequence repeat markers in 300 Caucasians, identifying HTR2B gene as a candidate for drug abuse vulnerability. RESULTS: From DNA re-sequencing of 110 subjects, we discovered three novel single nucleotide polymorphisms (SNPs), two of which confer a double-mutant of the receptor protein in a drug-abusing population. Arg6, a conserved basic residue, and the conserved acidic Glu42 are mutated simultaneously into Gly, termed R6G/E42G. Furthermore, this double-mutant tends to associate with drug abuse (P = 0.08 by chi2 test). The third SNP that is a synonymous mutation in the codon of Gln11 showed significant association with drug abuse (P = 0.0335 by Fisher's exact test). CONCLUSION: Our data are the first suggesting that HTR2B contributes to brain architecture and pathways that are involved in illegal drug reward.
Keywords: genetická variace; poruchy spojené s užíváním psychoaktivních látek; běloši; lidé; Codon; Humans; alely; sekvenční analýza DNA; kodon; Gene Frequency; frekvence genu; Sequence Analysis, DNA; Polymorphism, Single Nucleotide; Alleles; Adult; Genetic Variation; Glycine; genetické markery; Receptor, Serotonin, 5-HT2B; Amino Acid Substitution; Cohort Studies; substituce aminokyselin; jednonukleotidový polymorfismus; Microsatellite Repeats; White People; glycin; Substance-Related Disorders; dospělí; kohortové studie; mikrosatelitní repetice; receptor serotoninový 5-HT2B; Genetic Markers